Math Problem Statement
𝑝∨𝑞∧(𝑟∨𝑝)∧𝑟
Solution
Let's simplify the logical expression step by step:
The given expression is:
Step 1: Apply parenthesis
First, let's look at the parentheses: So, the expression becomes:
Step 2: Understand precedence
We need to be aware of the precedence of the logical operations:
- The AND () operation has higher precedence than OR ().
- So, the expression should be handled in this order:
- Then,
- Finally, apply the ORs with .
Let’s break it down more clearly:
-
First, we handle , which will be: This doesn't simplify directly unless we know the truth values of , , and .
-
Next, simplify . This can be simplified using the distributive property: since and (because is present in both).
Step 3: Final simplification
Now, we substitute this back into the original expression:
Final Expression:
Thus, the simplified expression is:
This is the most simplified version of the expression.
Questions:
- What would happen if you had a NOT operation in this expression?
- How do you simplify expressions with more than three variables?
- Can this simplification be proven by truth tables?
- How would the simplification change if was false?
- How does associativity affect logical expressions?
Tip:
Always pay attention to the precedence of logical operators when simplifying expressions. (AND) always takes precedence over (OR), so break down the expressions accordingly.
Let me know if you need further clarification or if you have any other questions!
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Logic
Boolean Algebra
Logical Expressions
Formulas
Distributive property
Precedence of logical operators (AND, OR)
Theorems
Distributive property of logical operators
Precedence of AND over OR in logical expressions
Suitable Grade Level
Grades 9-12
Related Recommendation
Simplifying Logical Expression ¬p ∨ r ∧ (p ∨ q)
Distributing Boolean Expressions: Simplifying (p∧q) ∧ (p∨q)
Simplification of the Logical Expression (p∨~q)∧(~p∨~q)∨q
Simplifying Propositional Logic Expression: ¬q ∨ ((p ∧ ¬r) ∨ (p ∧ ¬q))
Simplifying the Logical Expression (q → p) ∧ ¬(r ∧ q) Using Logical Equivalences